Fanconi anemia gene editing by the CRISPR/Cas9 system - Osborn, Mark J.; Gabriel, Richard; Kalle, Christof von; Schmidt, Manfred (Human gene therapy, 2014)
Genome engineering with designer nucleases is a rapidly progressing field, and the ability to correct human gene mutations in situ is highly desirable. We employed fibroblasts derived from a patient with Fanconi anemia as a model to test the ability of the clustered regularly interspaced short palindromic repeats/Cas9 nuclease system to mediate gene correction. We show that the Cas9 nuclease and nickase each resulted in gene correction, but the nickase, because of its ability to preferentially mediate homology-directed repair, resulted in a higher frequency of corrected clonal isolates. To assess the off-target effects, we used both a predictive software platform to identify intragenic sequences of homology as well as a genome-wide screen utilizing linear amplification-mediated PCR. We observed no off-target activity and show RNA-guided endonuclease candidate sites that do not possess low sequence complexity function in a highly specific manner. Collectively, we provide proof of principle for precision genome editing in Fanconi anemia, a DNA repair-deficient human disorder.